Development of Students' Self-Educational Activities in The Conditions of Education Informatization - Rakhimov, Bakhtiyor; Isaeva, Guli; Nosirova, Dilfuza; Fayzieva, Shoira; Erkaeva, Munavvar 二 (International Journal of Psychosocial Rehabilitation, 2020)
This article is written with the aim of developing self-educational activities of students in the conditions of informatization of education. The following main objectives of the study are identified in the article: to determine the degree of elaboration of the problem and to identify the socio-historical prerequisites for the development of students' self-educational activities in the context of computerization of education; to reveal the content of the fundamental concepts of research: “self-educational activity”, “innovative self-educational environment”, “automated educational complexes”; determine the conditions and boundaries of pedagogical expediency of using information technology tools, as well as identify patterns and the degree of their influence on the success of the development of students' self- educational activities; theoretically substantiate a motivational-activity approach that determines the development strategy of students' self-educational activities in the context of education informatization; to develop and theoretically substantiate the pedagogical concept of the development of self-educational activities of students in the conditions of informatization of education; to develop a model, identify patterns and justify the technology for the development of self-educational activities of students in the conditions of informatization of education; to identify and justify the possibilities of the innovative self- educational environment of the university to create optimal conditions for the development of self- educational activities of students.